2007
DOI: 10.1111/j.1745-4557.2007.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cloud Components From Selected Tropical Fruits

Abstract: The composition and characteristics of insoluble fruit matter (IFM) and alcohol insoluble solids (AIS) from banana, mango and orange were evaluated. The galacturonic acid content was significantly higher for mango and orange pectin (6.0%) compared to banana (5%). The degrees of esterification of pectin in AIS were 78 Ϯ 5, 85 Ϯ 6 and 85 Ϯ 2 for mango, orange and banana, respectively. Proteins in the fruit pulps were of low molecular weight (<100,000 Da). The relative proportions of the amino acids in the AIS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Similar results were observed in apple fruit where flavonols were localized at the early stage of fruit development 30 . Similar to our study, naringenin, catechin and epicatechin has been previously reported in banana by other researchers 57 58 59 . The analysis suggested that PAs and transcripts associated with their biosynthesis ( MaANR and MaLAR ) were abundant at the early developmental stages of the fruit.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were observed in apple fruit where flavonols were localized at the early stage of fruit development 30 . Similar to our study, naringenin, catechin and epicatechin has been previously reported in banana by other researchers 57 58 59 . The analysis suggested that PAs and transcripts associated with their biosynthesis ( MaANR and MaLAR ) were abundant at the early developmental stages of the fruit.…”
Section: Discussionsupporting
confidence: 93%
“…Naringin, previously reported in banana pulp, was not detected in any of the cultivars that were analyzed in the current study. The total phenolics levels (6.5−18.9 mg of GAE g −1 of dry weight) are lower than the lowest values that have been previously reported (11.8 mg g −1 of fresh weight) , but the total phenolic levels previously reported have varied greatly depending on the cultivar and the method of extraction and analysis used .…”
Section: Resultsmentioning
confidence: 59%
“…Recent studies have shown that there are significant levels of total free phenolics in the pulp ranging from 11.8 to 90.4 mg of gallic acid equivalents 100 -1 g of fresh weight (5). An evaluation of banana pulp as a source of cloud components for the juice industry also revealed that bananas have high phenolic content (138 mg of gallic acid equivalents L -1 ) (6). Banana fruit pulp has also been found to have significant levels of total cell wall bound phenolics (ethyl acetate-soluble cell wall phenolics) (4.4 mg of gallic acid equiva-lents 100 -1 g of cell wall) and water-soluble cell wall phenolics (29.9 mg of gallic acid equivalents 100 -1 g of cell wall) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Pectic substances are complex, high‐molecular‐weight, heteropolysaccharide plant cell wall constituents comprised α‐1,4‐linked D‐galacturonic acid and L‐rhamnose linear chains with oligosaccharide branched side chains consisting of arabinose, galactose, and xylose (Willats and others 2001). Interestingly, Koffi and others (2007) reported that galactose is the major monosaccharide constituent of the alcohol‐insoluble fraction of frozen Valencia orange pulp, comprising 10.40%± 0.05% by weight. These data show that although the derived concentations of free galactose typical for apple and orange juice should be approximately 0.3 – 1.1 mM, those concentrations could be sufficient to allow binding to ricin B subunit (K d 35 μM).…”
Section: Resultsmentioning
confidence: 99%